Extraction, separation and identification of anthocyanins from red wine by-product and their biological activities. (August 2016) - Trikas, Evangelos D.; Melidou, Maria; Papi, Rigini M.; Zachariadis, George A.; Kyriakidis, Dimitrios A.
Highlights: Significantly higher TEAC corresponds to 1 g of byproducts compared to 1 mL of wine. Biological activity of isolated fractions is attributed to synergistic interactions. Both extracts exhibited high antibacterial activity against all 4 tested bacteria. One third of byproduct extract's anti-COX-2 activity was attributed to anthocyanin content. Results highlighted the potential for better utilization of these byproducts wastes. Abstract: By-products of grape processing constitute the major disposal problem of winery industries. However, these by-products could be used as a source of the phenolic compounds that are responsible for the beneficial effects of wine. The aim of this work was to utilize these wastes, namely red grape pomace, by extracting high-added value natural products, the anthocyanins. The exact anthocyanin content of the extract was determined; 21 anthocyanins were identified using liquid chromatography coupled with photodiode array and mass spectrometry (HPLC-PDA-MS), and its dominant anthocyanins [malvidin-3-O-glucoside, malvidin-3-(6″-acetylglucoside) and malvidin-3-(6-O-p-coumaroylglucoside)] were isolated and collected in three different fractions that contained the compounds of interest at relative concentrations above 80%. The antioxidant, antibacterial, and anti-inflammatory activity of the extract, the fractions, and standard compounds were evaluated while experiments were performed to compare these results with those of the wine variety (Syrah) from which the specific byproducts were produced. Both the by-products extract and condensed wine exhibited high antibacterial activity against the tested bacteria, as well as anti-inflammatory activity against COX-1 and COX-2. Furthermore, the antioxidant activity results suggested a synergistic effect among phenolic compounds, while it was also estimated that 1 gram of by-products corresponds to 6.79 mM Trolox, a higher value compared to the 0.12 mM Trolox of 1 millilitre of wine.